2011
DOI: 10.1002/jor.21525
|View full text |Cite
|
Sign up to set email alerts
|

The interrelation of trabecular microstructural parameters of the greater tubercle measured for different species

Abstract: In the present study the trabecular microstructural parameters (bone volume fraction, trabecular thickness, trabecular separation, trabecular number, connectivity density, degree of anisotropy, and structure model index) of the greater tubercle of the humeral head were measured for human healthy, human osteopenic, ovine, bovine, and porcine bones using micro-computed tomography. Except for trabecular thickness and degree of anisotropy the values of the trabecular microstructural parameters generally differed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The 10‐week‐old Sca‐1 −/− mice were transplanted with 2 × 10 6 WT MSCs and assessed 24 weeks later, at 8.5 months of age, the time point when the osteopenic condition peaks in Sca‐1 −/− mice [26]. Computed tomography (CT) is used clinically to identify microarchitectural aberrations in trabecular tissue associated with human aging and osteoporosis [36, 37]. Here, we performed microCT analyses on the proximal tibias of mice transplanted with WT MSCs, along with WT and naïve Sca‐1 −/− controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 10‐week‐old Sca‐1 −/− mice were transplanted with 2 × 10 6 WT MSCs and assessed 24 weeks later, at 8.5 months of age, the time point when the osteopenic condition peaks in Sca‐1 −/− mice [26]. Computed tomography (CT) is used clinically to identify microarchitectural aberrations in trabecular tissue associated with human aging and osteoporosis [36, 37]. Here, we performed microCT analyses on the proximal tibias of mice transplanted with WT MSCs, along with WT and naïve Sca‐1 −/− controls.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we performed microCT analyses on the proximal tibias of mice transplanted with WT MSCs, along with WT and naïve Sca‐1 −/− controls. Trabecular connectivity‐density (Conn.D), a measure of the interconnectivity of trabecular structures that provides strength to bone, displays a characteristic decline in osteoporosis [36]. Sca‐1 −/− mice presented with significantly lower connectivity‐density versus WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, porcine-derived bone graft materials have only recently been developed and marketed. It has been reported that porcine bone has a similar formulation and structure to human bone [ 5 ]. The lipid content (in terms of category and structure) of porcine bone is also similar to that of human bone [ 6 ].…”
Section: Introductionmentioning
confidence: 99%